VD_FINDINFO HC / 2015 / 836 vom 18. September 2015 - VD Tribunal cantonal (2015)
NOVA, APPELCPC, CHARGE FISCALE, MINIMUM VITAL, REVENU NET, JARDINIER, EXCÉDENT | 176 al. 1 ch. 1 CC, 317 al. 1 CPC (CH)